Non-communicable Diseases and Cognitive Impairment: Pathways and Shared Behavioral Risk Factors Among Older Chinese - Yiengprugsawan, Vasoontara Sbirakos; Browning, Colette Joy (Frontiers in Public Health, 2019)
Population ageing has brought about a number of challenges for public health and primary health care systems, including increases in the prevalence of non-communicable diseases (NCDs). As a country with one of the largest populations globally, China is confronting a rising number of chronic NCDs including cardiometabolic related conditions. This mini-review investigates the link between NCDs and cognitive and mild cognitive impairment (CI/MCI) through common risk factors. Identiyfing risk factors is important for the prevention and management of theses chronic conditions. The review also identifies the role of primary health care services in reducing behavioural risk factors for NCDs and CI/MCI. Addressing shared determinants and pathways is important in the design of public health interventions and primary health care services in China. Monitoring and management of NCDs biomarkers and behavioural risk factors could also be beneficial for the cognitive health among older Chinese.